2007
DOI: 10.1128/jb.00655-07
|View full text |Cite
|
Sign up to set email alerts
|

Complementation Analysis of the Cold-Sensitive Phenotype of the Escherichia coli csdA Deletion Strain

Abstract: The cold shock response of Escherichia coli is elicited by downshift of temperature from 37°C to 15°C and is characterized by induction of several cold shock proteins, including CsdA, during the acclimation phase. CsdA, a DEAD-box protein, has been proposed to participate in a variety of processes, such as ribosome biogenesis, mRNA decay, translation initiation, and gene regulation. It is not clear which of the functions of CsdA play a role in its essential cold shock function or whether all do, and so far no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
86
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 39 publications
5
86
1
Order By: Relevance
“…Again, this effect was counteracted by overexpression of the wild-type CsdA, but not helicase-deficient CsdA mutants. 90 We used csdA deletion cells and screened an E. coli genomic library for protein(s) that can complement the essential CsdA function during cold acclimation. We observed that another DEAD-box RNA helicase, RhlE, complemented the csdA deletion.…”
mentioning
confidence: 99%
“…Again, this effect was counteracted by overexpression of the wild-type CsdA, but not helicase-deficient CsdA mutants. 90 We used csdA deletion cells and screened an E. coli genomic library for protein(s) that can complement the essential CsdA function during cold acclimation. We observed that another DEAD-box RNA helicase, RhlE, complemented the csdA deletion.…”
mentioning
confidence: 99%
“…This scenario would explain the earlier complementation data. What has not been easy to explain is how RNase R lacking its nuclease activity is still able to complement a csdA deletion (11). We have now found in vitro that at high levels, nuclease-deficient RNase R can complement because it converts a duplex substrate to single strands, which then are easily digested by PNPase and RNase R (data not shown).…”
Section: Discussionmentioning
confidence: 77%
“…We have now found in vitro that at high levels, nuclease-deficient RNase R can complement because it converts a duplex substrate to single strands, which then are easily digested by PNPase and RNase R (data not shown). If a similar situation occurs in vivo, such a mechanism would allow PNPase and the WT RNase R present in the strain to function in the absence of CsdA and lead to the apparent complementation by nuclease-deficient RNase R that was observed (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations